Overcoming Quality Control Challenges in Car Exhaust Manufacturing: Mengatasi Tantangan Kontrol Kualitas dalam Pembuatan Knalpot Mobil - Setiono, Moch. Agung; Cahyana , Atikha Sidhi (Universitas Muhammadiyah Sidoarjo, 2024)
PT. XYZ, a manufacturer of car exhaust components, faces significant defect-related challenges, impacting productivity and market competitiveness, particularly in Europe. Over six months, 3.18% of 184,708 produced components were defective. This study aims to determine the sigma level of quality control and identify root causes of defects using the Six Sigma DMAIC method and Root Cause Analysis (RCA). Observations and interviews revealed human error, machine issues, improper methods, substandard materials, and environmental factors as key contributors to defects. The sigma level was found to be 4, indicating suboptimal quality control. Recommendations for improvement include SOP development, operator training, standardized production methods, regular machine maintenance, and 5S organizational practices. Implementing these could reduce defects and improve productivity. Highlight: Defect Rate: 3.18% in 184,708 components. Sigma Level: Evaluated at level 4. Improvements: Implement SOPs, training, maintenance, 5S practices. Keyword: Quality Control, Six Sigma, Root Cause Analysis, Manufacturing, Car Exhaust Components